System of Book Recommendation in Library by Using Natural Language Processing - Kumpaor, Natsuda; Ketcham, Mahasak (Journal of Advanced Development in Engineering and Science, 2023)
The purposes of this research are 1) to develop recommend in library by using natural language processing, 2) to evaluate the developed system efficiency and 3) to evaluate the satisfactory of the users to the developed system. Therefore, the system was developed as web application by using PHP programming language and MySQL as a database management. The accuracy of the developed system was tested by 5 experts and 50 general users. The result showed that the developed system provided 98.72 percent accuracy, which is more than the set up accuracy threshold of 97.5 percentages. The overall satisfaction of the system evaluated by 5 experts and 50 general users was in the highest level with the mean score of 4.53 (the standard deviation of 0.507)